DIGITAL CREATIVITY AND SOCIAL VALUE CREATION: ENTREPRENEURIAL STRATEGIES IN TECHNOLOGY-DRIVEN COMMUNITIES - Eko Cahyo Mayndarto; Ren Suzuki; Miku Fujita; Indra Dermawan (Yayasan Adra Karima Hubbi, 2026)
The rise of digital technologies has revolutionized entrepreneurial strategies, enabling the integration of creativity into business models that address social challenges. Digital creativity is now a vital tool for fostering social value in technology-driven communities. This research explores how entrepreneurs leverage digital creativity to create social value, focusing on sectors such as health, sustainability, and cultural preservation. The study aims to investigate the relationship between digital creativity and social value creation within entrepreneurial strategies. A qualitative approach was employed, utilizing case studies, semi-structured interviews, and document analysis of 10 digital platforms from various technology-driven sectors. The findings reveal that digital creativity not only contributes to business success but also facilitates community engagement, empowerment, and the development of social initiatives. Platforms with a focus on transparency and active community participation showed higher levels of social value creation, particularly in health and sustainability sectors. The study concludes that digital creativity in entrepreneurial strategies is an effective driver of social change and can contribute to sustainable development. Furthermore, the research emphasizes the importance of balancing profit with social impact, offering a framework for integrating digital creativity into business practices for broader societal benefits.